Contrast-enhanced ultrasound for characterizing renal masses. Issue 105 (August 2018) - Bertolotto, Michele; Bucci, Stefano; Valentino, Massimo; Currò, Francesca; Sachs, Camilla; Cova, Maria Assunta
Highlights: On cross-sectional imaging studies performed for other indications, incidental discovery of renal lesions is common. Contrast-enhanced ultrasound (CEUS) has become a powerful additional tool for the assessment of renal masses. Established applications of CEUS in imaging renal masses are differentiation between solid tumors, pseudolesions, and complex cysts; characterization of complex cysts with different malignant potential, and evaluation of tumour ablation. Microbubble contrast agents are safe. Adverse reactions are rare. Abstract: On cross-sectional imaging studies performed for other indications, incidental discovery of renal lesions is not uncommon. In daily use, grey-scale ultrasonography (US) and conventional Doppler modes are often the modality of choice for the initial assessment. While simple cysts are fully characterized with US, other lesions require further characterization, which is traditionally obtained by multiphase imaging, such as contrast-enhanced CT and MRI. Contrast-enhanced ultrasound (CEUS) has become a powerful additional tool for imaging renal lesions. With its lack of nephrotoxicity, the absence of ionizing radiation, and the ability to evaluate the enhancement pattern of renal lesions quickly and in real- time, CEUS has unique advantages over traditional modes. Established applications are differentiation between solid tumours, pseudolesions, and complex cysts; characterization of complex cysts with different malignant potential, and evaluation of tumor ablation. Microbubble contrast agents are safe. Adverse reactions are rare. This article provides an overview of the current clinical applications of CEUS in characterizing renal masses, discussing advantages and limitations. The aim is to provide the framework for sonologists to make informed decisions regarding this emerging imaging test in appropriate circumstances.